Epigenetic Mechanisms in Irritable Bowel Syndrome - Mahurkar-Joshi, Swapna; Chang, Lin (Frontiers in Psychiatry, 2020)
Irritable bowel syndrome (IBS) is a disorder of brain-gut interactions characterized by abdominal pain and altered bowel habits. IBS is a multifactorial disease with evidence for familial clustering attributed to genetic or shared environmental factors. However, there are weak genetic associations reported with IBS and a lack of evidence to suggest that major genetic factor(s) contribute to IBS pathophysiology. Studies on animal models of stress, including early life stress, suggest a role for environmental factors, specifically, stress associated with dysregulation of corticotropin releasing factor and hypothalamus-pituitary-adrenal (HPA) axis pathways in the pathophysiology of IBS. Recent evidence suggests that epigenetic mechanisms, which constitute molecular changes not driven by a change in gene sequence, can mediate environmental effects on central and peripheral function. Epigenetic changes include alterations in DNA methylation, histone modifications, and differential expression of non-coding RNAs (microRNA [miRNA] and long non-coding RNA) among others. Here we review the role of molecular factors in the pathophysiology of IBS with a focus on epigenetic mechanisms. Emerging evidence for epigenetic changes in IBS includes changes in DNA methylation in animal models of IBS and patients with IBS, and various miRNAs that have been associated with IBS and endophenotypes such as increased visceral sensitivity and intestinal permeability. DNA methylation, in particular, is an emerging field in the realm of complex diseases and a promising mechanism which can provide important insights into IBS pathogenesis and identify potential targets for treatment.